VILLAGE ASSETS MANAGEMENT BY THE GOVERNMENT OF CITEUREUP VILLAGE KAWALI DISTRICT CIAMIS REGENCY: Array - Ari Prayoga; Supri (JGSRD: Journal of Government Science and Rural Development, 2022)
Citeureup Village is one of the villages in the Kawali sub-district, Ciamis Regency which carries out village asset management. Problem encounteredthere is still a lack of undirected planning and strategies related to the management of village assets by the Citeureup Village Government so that they do not know what to do and what kind of village asset management is carried out in order to achieve optimal results, village land and village treasury land have not been legally certified, there is still a lack of proper understanding. owned by the village asset manager, and there is still a lack of potential exploration of the village assets owned. The purpose of this study was to determine the management of village assets by the Citeureup Village Government, Kawali District, Ciamis Regency. This research is not optimal management of village assets by the Citeureup Village Government, Kawali District, Ciamis Regency.The theory used is the theory of Hanif Nurcholis which shows that the management of village wealth is carried out based on functional principles, legal certainty, openness, efficiency, accountability, and value certainty. The research method used in this study is a descriptive qualitative research method. According to Sugiyono, research using descriptive methods can be given to a single variable, namely without making comparisons or connecting with other variables. In this study the authors used a qualitative approach. The author chooses to use a qualitative approach, because in this study the author places more emphasis on investigation to understand social problems. Data collection methods used are observation, interviews, and documentation.in terms of benefits for increasing the village's original income, it is often still not optimal and often jams. The implementation of village asset management still does not pay attention to the applicable village regulations. In addition, the legal proof of ownership of village assets such as land certificates has not been fulfilled and has not been carried out. Regarding the website, it still does not provide complete and up-to-date information for the community because updates from the village government are old. Pamsimas management has not carried out written reports. Calculation of the amount, value and condition of assets is often hampered because there is still a lack of quantity of managing human resources.